Persistence of indoxacarb and thiacloprid residues on brinjal during Kharif season under mid-hill conditions of Himachal Pradesh - Sharma, Sugandha; Sharma, Prem Chand; Chandel, Y S (Indian Journal of Plant Protection, 2020)
The present studies were carried out at CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur to observe the persistence pattern of two insecticides and suggest their suitable waiting periods. The residues were worked out during Kharif season of year 2016 and 2017 on brinjal fruits at 0, 1, 3, 5, 7, 10 and 15 days after application of insecticides. The residues were analyzed using Reverse Phase High Performance Liquid Chromatography (RP-HPLC). The initial deposits of indoxacarb (0.01%) on brinjal fruits were found to be 0.620±0.025 and 0.622±0.015 mg/kg during 2016 and 2017, respectively. The residues were below detectable limits on 10th day of spray. The average half-life value of indoxacarb residues on brinjal was found to be 1.31 and 1.29 days during 2016 and 2017, respectively. The initial deposits of thiacloprid (0.03%) on brinjal fruits during 2016 and 2017 were found to be 1.078±0.011 mg/kg and 1.133±0.044 mg/kg, respectively. The reported concentration declined with time and reached non-detectable after 10-15 days. The half-life value of thiacloprid residues was 2.55 (2016) and 2.47 (2017) days. The safety interval for indoxacarb was worked out to be 0.4 days and for thiacloprid 1.6 and 1.7 days during 2016-17, respectively. Therefore, a waiting period of 1 day for indoxacarb and 2 days for thiacloprid is suggested for safe consumption of brinjal fruits.